What aspects of solar flares can be clarified with mm/submm observations? - Fleishman, Gregory D.; Martinez Oliveros, Juan Carlos; Landi, Enrico; Glesener, Lindsay (Frontiers in Astronomy and Space Sciences, 2022)
This paper identifies several unsolved questions about solar flares, which can potentially be answered or at least clarified with mm/submm observations with ALMA. We focus on such questions as preflare phases and the initiation of solar flares and the efficiency of particle acceleration during flares. To investigate the preflare phase we propose to employ the extraordinary sensitivity and high spatial resolution of ALMA, which promises to identify very early enhancements of preflare emission with high spatial resolution and link them to the underlying photospheric magnetic structure and chromospheric flare ribbons. In addition to revealing the flare onsets, these preflare measurements will aid in the investigation of particle acceleration in multiple ways. High-frequency imaging spectroscopy data in combination with the microwave data will permit the quantification of the high-energy cutoff in the nonthermal electron spectra, thus helping to constrain the acceleration efficiency. Detection and quantification of secondary relativistic positron (produced due to nonthermal accelerated ions) contribution using the imaging polarimetry data will help constrain acceleration efficiency of nonthermal nuclei in flares. Detection of a ``mysterious’’ rising spectral component with high spatial resolution will help determine the emission mechanism responsible for this component, and will then help in quantifying this either nonthermal or thermal component of the flaring plasma. We discuss what ALMA observing mode(s) would be the most suitable for addressing these objectives.